2018
DOI: 10.20473/ijdm.v1i2.2018.70-80
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combination of Soy Milk and Calcium in Orthodontic Tooth Movements on Female Rats With Estrogen Deficiency

Abstract: Background: Orthodontic treatments in elderly patients are influenced by hormonal changes and their effects on the process and prognosis of the treatment. Estrogen deficiency in the post-menopausal period results in bone loss. The process of bone remodeling during Orthodontic treatment for elderly patients is also influenced by the balance of resorption and bone formation processes. Purpose: This study aimed to determine the effect of soymilk combination calcium on orthodontic tooth movement in female rats wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Natural and Life Sciences Communications: https://cmuj.cmu.ac.th sialoprotein (Ramadhani et al, 2018). Sitasari et al (2020) showed an increase in OSX expression on day 14 compared to that on day 7 after the administration of green tea extract.…”
Section: Groupsmentioning
confidence: 99%
“…Natural and Life Sciences Communications: https://cmuj.cmu.ac.th sialoprotein (Ramadhani et al, 2018). Sitasari et al (2020) showed an increase in OSX expression on day 14 compared to that on day 7 after the administration of green tea extract.…”
Section: Groupsmentioning
confidence: 99%